Characterization and Three Dimensions of the Main Character in Looking for Alaska - Suardi Utama, I Ketut (Humanis; Vol 22 No 1 (2018)DO - 10.24843/JH.2018.v22.i01.p15, 2018)
This study is entitled “Characterization and Three Dimensions of the Main Character in Looking For Alaska”. This study is concerned with the method of the characterization based on the three dimensions of the main character and intrinsic elements in the novel. The main purpose of this study is to find out how the author presents the main character in terms of the physiological, psychological, and sociological dimensions. This study was based on library research and used documentation method in collecting data. Then the data obtained were analyzed descriptively using descriptive qualitative method. Some theories of characterization were used such as the theory of characterization proposed by Kenney (1966), the theory of character dimensions by Egri (1960). The data source of this study is a novel entitled Looking For Alaska by John Green (2011). The analysis started with the overview of the biography of John Green and that was followed by the synopsis of the novel, and the data was categorized based on the theories. Based on Kenney’s theory, the main character is shaped through the mixing method of the characterization. In addition, based on Egri’s theory, there are three character dimensions (physiological, psychological, and sociological) involved in the shaping and presentation of the main character.